Beyond the climate science: CCAFS downscaled climate data applied by development agencies around the world - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
In sub-Saharan Africa and South Asia, the limited availability of climate data and networks for sharing information can serve as a constraint to agricultural research and development. The lack of basic understanding of earth processes needed to detect flaws in climate models and decide how best to combine climate and crop models in research is another constraint. In order to address these contraints, CCAFS reviewed the knowledge on climate data and crop modelling and ways of coupling agriculture– climate predictions. The result was the successful development of CCAFS-Climate, a data portal that has become the place to get free and open-access downscaled climate data useful for understanding the effects of climate change on agriculture. The portal includes the MarkSim GCM tool, which generates plausible daily data for future climates. Since its launch, the CCAFS-Climate portal has become popular among the research community as well as with other stakeholder groups. Almost 1700 institutions from 185 countries have used the portal for a range of purposes, including: studying climate change impacts at the country-level for informing decision makers, government planning, informing crop insurance policy development, and water policy development. The users included around 400 non-research institutions from 60 countries, indicative of the portal’s popularity outside of the research community.